THE IMPACT OF TRADE FACILITATION INDICATORS ON TRADE BETWEEN CEFTA-2006 MEMBERS - Toshevska trpchevska, Katerina; Makrevska disoska, Elena; Kikerkova, Irena; Tonovska, Jasna (My University, 2022)
The European financial and economic crisis interrupted the boost of trade within CEFTA-2006, and diverted trade flows from within the region toward the EU market. Currently, Western Balkan economies record a high level of economic integration with the EU which accounts for almost 2/3 of their total trade exchange of goods, while the trade exchange within CEFTA -2006 falls between 10-15% of the total trade exchange of goods of its member-states. Changes in the legal texts of CEFTA-2006 initiated by the so-called Berlin Process, and the effort for deepening regional integration according to the latest Action Plan (2020) envisaged the creation of a Common Regional Market based on EU rules by 2024. The impact of the creation of a Common Regional Market within CEFTA-2006 upon the economic welfare of each of the member-states is still unclear. Thus all estimations provided vague, ambiguous and unclear results and recommendations which did not help overcome the already present reluctant attitude. The latest 2021 Open Balkan Initiative in which participate only Albania, Macedonia and Serbia brought even more confusion and resentment by the other four CEFTA-2006 member-states. The aim of this paper is to elaborate the possibilities that might be open by the latest regional integration initiatives in regard of boosting regional trade exchange of goods. In the last two decades, it was recognized that enhanced trade liberalization might be achieved by undertaking trade facilitation measures. The effects of the implementation of these measures are expected to be of greater significance for increasing regional trade exchange in comparison to the elimination of all other trade barriers, including tariffs. Previous research in this field confirmed that the elimination of certain customs and administrative barriers within the Western Balkan region had a significant positive impact on trade. We apply the gravity model of international trade to estimate the impact of OECD Trade Facilitation Indicators on trade among CEFTA-2006 members: Albania, Bosnia and Hercegovina, Montenegro, Moldova, North Macedonia, and Serbia. These indicators cover a great spectrum of border procedures for more than 160 economies across different income levels, geographical regions, and levels of development. Each Trade Facilitation Indicator is composed of several specific, precise, and fact-based variables related to existing trade-related policies and regulations and their implementation in practice. The analysis will be based upon twelve Trade Facilitation Indicators, separately evaluated by the individual relevance of each of them for the regional trade exchange.
Keywords: CEFTA-2006, OECD Trade Facilitation Indicators, trade facilitation, gravity model